Evaluation of heavy metal uptake by senduduk (Melastoma malabathricum) as a phythoremediator of soil contaminated with sewage sludge - Mamat, Shairani (2016)
Phytoremediation is the use of plants to remediate pollutants from soils and this approach has not been widely practiced in Malaysia. This study was conducted in a greenhouse, at the Faculty of Forestry, Universiti Putra Malaysia. The objectives of this study were: (i) to examine the ability of Melastoma malabathricum for taking up heavy metals from soil contaminated with sewage sludge in the growth medium after harvesting period and (ii) to evaluate the potential of M. malabathricum as a phytoremediator plant in taking up heavy metals and translocate heavy metal elements in plant parts (leaves, stems, roots) by using an indicator of Translocation factor (TF) and Bio-concentration factor (BCF). M. malabathricum were germinated at the greenhouse for two months prior transplanting into growth media (soil + sewage sludge) for six months. The seedlings were planted on six different growth media (soil + different levels of sewage sludge) namely; control T0-Control (100% soil), T1 (80% soil and 20% of sewage sludge), T2 (60% soil and 40% of sewage sludge), T3 (40% soil and 60% of sewage sludge), T4 (20% soil and 80% sewage sludge) and T5 (100% sewage sludge). Each type of treatments was replicated for four times. pH both of growth media was determined using galss electrode whereas the concentrations of heavy metals consist of copper (Cu), lead (Pb) and Zinc (Zn) in the growth media were analyzed using atomic absorption spectrometer (AAS). The pH increased after harvesting (5.39 to 6.43), compared to before planting (5.17 to 6.13). The highest value is T5 (6.43), followed by T4 (6.31) and the lowest T0 (5.39). M. malabathricum are able to uptake heavy metals (Cu, Pb and Zn). The results showed that there the concentrations of heavy metals among treatments before planting and after harvesting were significant differences whereby before planting the highest concentration of Cu was detected at T5 (3.93 mg kg-1) followed by T4 (2.90 mg kg-1), T3 (2.34 mg kg-1) and the lowest is T0 (0.91 mg kg-1), whereas after harvesting, the Cu concentrations decreased in all treatments. The highest decreased was in T5 (1.50 mg/kg) and the lowest is T1 (0.26 mg kg-1). The highest concentration of Pb was found in T5 (9.54 mg kg-1) and the lowest is T0 (0.93 mg kg-1) before planting. After planting, the reduction was 0.26 mg kg-1 for T0 and 6.30 mg kg-1 for T5. For Zn, M. malabathricum was very effective in removing the heavy metal in T5 which is at the level of reduction was 14.28 mg kg-1. The highest accumulation of Cu in the plant parts was in root of T0 (0.13 mg kg-1) as well as Pb (0.94 mg kg-1) for T5. Studies showed that, the accumulation of Pb was high in the root. The highest accumulation of Zn in plant parts was found in stems at T0 (1.44 mg kg-1). Bioconcentration factors (BCF) and translocation factor (TF) for the three heavy metals (Cu, Pb and Zn) showed that BCF values were lower than 1, while TF above than 1, indicating that M. malabathricum is capable to translocate metals from roots to shoots and this study confirms that this species as a phytoextractor plant.